2021
DOI: 10.1177/0163278720983416
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Preventive Behaviors Index: Development and Validation in Two Samples From the United Kingdom

Abstract: Monitoring compliance with, and understanding the factors affecting, COVID-19 preventive behaviors requires a robust index of the level of subjective likelihood that the individual will engage in key COVID-19 preventive behaviors. In this article, the psychometric properties of the COVID-19 Preventive Behaviors Index (CPBI), including its development and validation in two samples in the United Kingdom, are described. Exploratory and confirmatory factor analyses were performed on data from 470 participants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 44 publications
3
57
0
1
Order By: Relevance
“…COVID-19 preventive behaviors were measured using a questionnaire on hand hygiene, wearing a mask, and distancing. Compared to prior studies that measured similar behaviors in adults ( Breakwell et al, 2021 ; Cvetković et al, 2020 ), this study showed low scores in hand hygiene and distancing, but not wearing masks, confirming the need to improve compliance with COVID-19 preventive behaviors in adolescents. Specifically, it was found that the score was exceptionally low on the item related to distancing (4.15 ± 1.12/3.99 ± 1.14 in previous studies vs. 2.97 ± 1.09 in the current study).…”
Section: Discussionsupporting
confidence: 61%
“…COVID-19 preventive behaviors were measured using a questionnaire on hand hygiene, wearing a mask, and distancing. Compared to prior studies that measured similar behaviors in adults ( Breakwell et al, 2021 ; Cvetković et al, 2020 ), this study showed low scores in hand hygiene and distancing, but not wearing masks, confirming the need to improve compliance with COVID-19 preventive behaviors in adolescents. Specifically, it was found that the score was exceptionally low on the item related to distancing (4.15 ± 1.12/3.99 ± 1.14 in previous studies vs. 2.97 ± 1.09 in the current study).…”
Section: Discussionsupporting
confidence: 61%
“…For example, Fear of COVID-19 Scale (Ahorsu et al, 2020 ; Bitan et al, 2020 ; Iversen et al, 2021 ; Magano et al, 2021 ). The COVID-19 Preventive Behaviors Index scale (Breakwell et al, 2021 ), Adolescent Conspiracy Beliefs Questionnaire (ACBQ) (Jolley et al, 2021 ). The Generic Conspiracist Beliefs Scale (GCBS-J) (Majima and Nakamura, 2020 ), Client trust in community health workers scale (CHWs) (Sripad et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Identity resilience is negatively related to internalized homonegativity and distress upon recall. This suggests that identity resilience may be protective against negative cognitive and affective states, such as internalized homonegativity and distress, which are in turn associated with the onset of identity threat (Breakwell, Fino & Jaspal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The Identity Resilience Index (Breakwell, Fino & Jaspal, 2021) comprising 16 items with responses on a 5-point scale (1 = strongly disagree to 5 = strongly agree) was used. Items included "On the whole, I am satisfied with myself" and "There is continuity between my past and present".…”
Section: Identity Resiliencementioning
confidence: 99%